2005
DOI: 10.1002/qua.20672
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the mechanism for spin‐forbidden quenching process O(1D) + CO2(1Σ) → O(3P) + CO2(1Σ)

Abstract: ABSTRACT:The mechanism of the spin-forbidden quenching process O(was investigated by ab initio quantum chemistry methods. The calculations showed the singlet potential surface [O( 1 D)ϩCO 2 ] is attractive where a strongly bound intermediate complex CO 3 is formed in the potential basin without a transition state, whereas the complex CO 3 that is formed on the triplet surface [O( 3 P)ϩCO 3 ] must overcome a barrier. The complex channel was documented by searching minimum energy intersection points in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Carbon trioxide CO 3 was identified in solid CO 2 and Ar matrix at low temperatures with IR absorption spectroscopy; the C 2 v bridged structure was deduced to be more stable than the D 3 h symmetric structure because only the former was observed. ,, A theoretical calculation of the system O( 1 D) + CO 2 supported this result . Calculations at various levels indicated that the energy difference between these two structures of CO 3 is within 1 kJ mol −1 , with a barrier of ∼18 kJ mol −1 from the most stable C 2 v structure for interconversion. ,, …”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Carbon trioxide CO 3 was identified in solid CO 2 and Ar matrix at low temperatures with IR absorption spectroscopy; the C 2 v bridged structure was deduced to be more stable than the D 3 h symmetric structure because only the former was observed. ,, A theoretical calculation of the system O( 1 D) + CO 2 supported this result . Calculations at various levels indicated that the energy difference between these two structures of CO 3 is within 1 kJ mol −1 , with a barrier of ∼18 kJ mol −1 from the most stable C 2 v structure for interconversion. ,, …”
Section: Introductionmentioning
confidence: 88%
“…26 Yang et al proposed that quenching of O( 1 D) by CO 2 occurs through a complex CO 3 as well as a direct collision process. 25 Here we present observations of the time-resolved IR emission spectra of product CO 2 from the quenching reaction of O( 1 D) by CO 2 . We found satisfactory agreement between observed emission spectra of CO 2 and those simulated based on a vibrational distribution of CO 2 predicted with a statistical theory.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations